Alpha-alumina carrier, preparation method of alpha-alumina carrier, silver catalyst and application of silver catalyst in preparation of ethylene oxide through ethylene epoxidation

By adding single-crystalline alumina to the alumina support and preparing silver catalysts, the problem of insufficient activity, selectivity and stability of the silver catalyst in the prior art is solved, and higher selectivity and stability are achieved, by-product emissions are reduced, and economic benefits are improved.

CN119701911AActive Publication Date: 2025-03-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202311265465.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28
Estimated Expiration
2043-09-27

AI Technical Summary

Technical Problem

In the process of ethylene oxidation of existing silver catalysts, the activity, selectivity and stability of ethylene oxide are insufficient, resulting in increased carbon dioxide emissions of by-products and low economic benefits.

Method used

The α-alumina support is prepared by adding an appropriate amount of single-crystalline flake alumina to the alumina support material, and the silver catalyst is prepared using the support to impregnate the silver compound.

Benefits of technology

It significantly improves the selectivity and stability of silver catalysts, reduces the emission of carbon dioxide by-products, improves the utilization rate of ethylene raw materials, and has a wide range of industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004474413890000061
    Figure BDA0004474413890000061
  • Figure BDA0004474413890000062
    Figure BDA0004474413890000062
Patent Text Reader

Abstract

The invention belongs to the field of silver catalysts, and relates to an alpha-alumina carrier, a preparation method thereof, a silver catalyst and application of the silver catalyst in preparation of ethylene oxide through ethylene epoxidation. The alpha-alumina carrier contains single crystal lamellar alumina, and the content of the single crystal lamellar alumina is 0.1-50 wt% on the basis of the total weight of the alpha-alumina carrier. The preparation method comprises the following steps: preparing a mixture containing micron-sized alumina, pseudo alumina monohydrate, a mineralizer and single crystal lamellar alumina, and mixing the mixture with an acid solution; and kneading the obtained material, performing extrusion molding, drying and roasting to obtain the alpha-alumina carrier. The silver catalyst prepared from the alpha-alumina carrier provided by the invention is used for preparing ethylene oxide through ethylene epoxidation, can significantly improve the selectivity and stability of the reaction, can significantly reduce the emission of a carbon dioxide by-product, improves the utilization rate of an ethylene raw material, and has a wide industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of silver catalysts, and specifically relates to an alpha-alumina carrier, a method for preparing the alpha-alumina carrier, the alpha-alumina carrier obtained by the method, a silver catalyst prepared from the alpha-alumina carrier, and application of the silver catalyst in preparing ethylene oxide by epoxidation of ethylene. Background Art

[0002] Ethylene oxidation under the action of silver catalyst mainly produces ethylene oxide, while side reactions produce carbon dioxide and water. Among them, activity, selectivity and stability are the main performance indicators of silver catalysts. Activity refers to the reaction temperature required when the ethylene oxide production process reaches a certain reaction load; the lower the reaction temperature, the higher the activity of the catalyst. Selectivity refers to the ratio of the number of moles of ethylene converted into ethylene oxide to the total number of moles of ethylene in the reaction. Stability is expressed as the rate of decrease of activity and selectivity. The smaller the rate of decrease, the better the stability of the catalyst. Using silver catalysts with high activity, high selectivity and good stability in the process of ethylene oxidation to produce ethylene oxide can greatly improve economic benefits. Therefore, the manufacture of silver catalysts with high activity, high selectivity and good stability is the main direction of silver catalyst research. In addition to the composition and preparation method of the catalyst, the performance of the silver catalyst is also closely related to the performance and preparation of the carrier used in the catalyst.

[0003] The preparation method of silver catalyst in the prior art includes two processes: preparation of a porous carrier (such as alumina) and loading active components and additives onto the carrier.

[0004] Adding other components to the alumina carrier to improve the performance of the silver catalyst is an important research direction, including adding alkaline earth metal oxides or other salt compounds. EP0150238 (US4428863) uses a small amount of barium aluminate or barium silicate binder in the manufacturing process of high-purity, low-surface alumina carrier, claiming that it can improve the crushing strength and wear resistance of the carrier. The specific surface area of ​​the prepared carrier is less than 0.3m 2 / g, the activity and selectivity of the prepared catalyst are relatively low. US5384302 claims that the crushing strength and wear resistance of the carrier can be improved by pre-treating α-Al2O3 to reduce the content of Na, K, Ca, and Al ions in the carrier. US5739075 pre-deposit a rare earth metal and another metal salt (alkaline earth metal or Group VIII transition metal) on the surface of the alumina carrier, and then calcine it, and finally make the treated carrier into a silver catalyst. The evaluation results show that the selectivity decrease rate of the catalyst is less than that of the catalyst sample without pre-deposition treatment.

[0005] As a mineralizer, fluoride is widely used in the preparation of alumina carriers. CN1034678A mixes α-alumina trihydrate and pseudo-monohydrate α-alumina with appropriate particle size and proportion, carbonaceous materials, flux, fluoride, binder and water, kneads them into a shape, and then dries and roasts them to make an α-alumina carrier. The specific surface area of ​​the carrier is 0.2 to 2 m 2 / g, pores with a pore radius greater than 30μm account for less than 25% of the total pore volume; after being impregnated with a silver compound and a promoter and dried and activated, this carrier is used for ethylene oxidation to produce ethylene oxide, with a selectivity of up to 83-84%. CN101007287A mixes α-alumina trihydrate, pseudo-monohydrate α-alumina of a certain particle size, a certain amount of combustible carbonaceous material, a flux, a fluoride, and an optional heavy alkaline earth metal compound, and after mixing evenly, adds a binder and water, kneads evenly, extrudes, and is dried and calcined to make an α-alumina carrier; the specific surface area of ​​the carrier is 0.2-2.0m 2 / g, pore volume is 0.35~0.85ml / g, water absorption rate is ≥30%, and crushing strength is 30~120N / grain. This carrier is impregnated with a solution of a silver amine complex, an alkali metal compound, and an alkaline earth metal compound, and after drying and activation, a silver catalyst is obtained for ethylene epoxidation to produce ethylene oxide. In the preparation of the carrier, CN1634652A does not use a pore-forming agent, but directly mixes α-alumina trihydrate with pseudo-monohydrate alumina, a flux, and a fluoride in a certain proportion, and after mixing evenly, a binder and water are added, kneaded evenly, extruded, dried and calcined to make an α-alumina carrier. The specific surface area of ​​the carrier made by this invention is 0.2~2.0m 2 / g, pore volume of 0.35-0.85ml / g, water absorption rate ≥30%, crushing strength of 20-90N / grain. The carrier is impregnated with a solution of a silver amine complex, an alkali metal compound and an alkaline earth metal compound, and after drying and activation, a silver catalyst is obtained for ethylene epoxidation to produce ethylene oxide.

[0006] Although the above patent documents respectively improve the alumina carrier by adding alkaline earth metal compounds to the alumina raw material or pre-depositing a rare earth metal additive on the surface of the alumina carrier, which brings different degrees of improvement to the activity or selectivity of the catalyst, with the large-scale industrial application of medium and high selectivity silver catalysts, the requirements for the performance of alumina carriers in this field are also constantly increasing. Summary of the invention

[0007] In view of the above-mentioned state of the prior art, the inventors of the present invention have conducted in-depth experimental research in the field of silver catalysts and alumina carriers thereof. As a result, it is found that the selectivity and stability of the silver catalyst made by adding an appropriate amount of single-crystal alumina to the carrier raw material to prepare the alumina carrier are significantly improved.

[0008] In order to achieve the purpose of the present invention, the first aspect of the present invention provides an α-alumina carrier, which contains single-crystalline alumina. Based on the total weight of the α-alumina carrier, the content of the single-crystalline alumina is 0.1 to 50 wt%, preferably 1 to 40 wt%, and more preferably 5 to 35 wt%.

[0009] A second aspect of the present invention provides a method for preparing an α-alumina carrier, comprising the following steps:

[0010] (1) preparing a mixture comprising micron-sized alumina, pseudo-monohydrate alumina, a mineralizer and single-crystal alumina, and mixing the mixture with an acid solution; based on the total weight of the mixture, the content of the micron-sized alumina is 4.5-90wt%, the content of the pseudo-monohydrate alumina is 5-95wt%, the content of the mineralizer is 0.01-3wt%, and the content of the single-crystal alumina is 0.1-50wt%;

[0011] (2) The material obtained in step (1) is kneaded, extruded, dried and calcined to obtain the α-alumina carrier.

[0012] The third aspect of the present invention provides an α-alumina carrier prepared by the preparation method of the α-alumina carrier.

[0013] The fourth aspect of the present invention provides a silver catalyst for producing ethylene oxide by ethylene oxidation, wherein the silver catalyst is prepared by impregnating the α-alumina carrier in a solution containing a silver compound.

[0014] A fifth aspect of the present invention provides an application of the silver catalyst in the epoxidation of ethylene to prepare ethylene oxide.

[0015] The silver catalyst prepared with the α-alumina carrier provided by the present invention is used for preparing ethylene oxide by epoxidation of ethylene, can significantly improve the selectivity and stability of the reaction, can significantly reduce the emission of carbon dioxide by-products, and improve the utilization rate of ethylene raw materials, and has broad industrial application prospects.

[0016] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0017] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0018] In order to achieve the purpose of the present invention, the first aspect of the present invention provides an α-alumina carrier, which contains single-crystalline alumina. Based on the total weight of the α-alumina carrier, the content of the single-crystalline alumina is 0.1 to 50 wt%, preferably 1 to 40 wt%, and more preferably 5 to 35 wt%.

[0019] According to the present invention, preferably, the α-alumina carrier has the following characteristics: a specific surface area of ​​0.3 to 3.0 m 2 / g, water absorption not less than 25%, mechanical strength not less than 30N.

[0020] In the present invention, the specific surface area of ​​the carrier is measured by the BET method, the water absorption rate is measured by the boiling method, and the mechanical strength is measured by the radial crushing method.

[0021] A second aspect of the present invention provides a method for preparing an α-alumina carrier, comprising the following steps:

[0022] (1) preparing a mixture comprising micron-sized alumina, pseudo-monohydrate alumina, a mineralizer and single-crystal alumina, and mixing the mixture with an acid solution; based on the total weight of the mixture, the content of the micron-sized alumina is 4.5-90wt%, the content of the pseudo-monohydrate alumina is 5-95wt%, the content of the mineralizer is 0.01-3wt%, and the content of the single-crystal alumina is 0.1-50wt%;

[0023] (2) The material obtained in step (1) is kneaded, extruded, dried and calcined to obtain the α-alumina carrier.

[0024] In the present invention, the addition of the mineralized material can accelerate the crystal transformation of aluminum oxide.

[0025] According to the present invention, preferably, in step (1), the particle size of the micron-sized aluminum oxide is 1 to 500 μm.

[0026] According to the present invention, preferably, in step (1), based on the total weight of the mixture, the amount of micron-sized alumina added is 23-80wt%, the amount of pseudo-monohydrate alumina added is 18-75wt%, the amount of mineralizer added is 0.1-2.5wt%, and the amount of single-crystal crystalline alumina added is 1-40wt%, preferably 5-35wt%.

[0027] According to the present invention, preferably, in step (1), the acid solution is an aqueous nitric acid solution, the volume ratio of nitric acid to water in the aqueous nitric acid solution is 1:1.25-10, preferably 1:2-8; the amount of the acid solution added is 5-50wt% based on the total weight of the mixture.

[0028] According to the present invention, preferably, the pseudo-alumina monohydrate and the acid solution are completely or partially replaced by aluminum sol.

[0029] In the present invention, the acid solution can react with pseudo-monohydrate alumina to form alumina sol, which is used as a binder. In a specific embodiment of the present invention, when the pseudo-monohydrate alumina and the acid solution can be completely replaced by alumina sol, the content of alumina sol in the mixture comprising micron-sized alumina, alumina sol, a mineralizer and single crystal alumina is 18-75wt%.

[0030] According to the present invention, preferably, the micron-sized alumina is selected from at least one of α-alumina trihydrate, β-alumina trihydrate and γ-alumina; the mineralizer is selected from at least one of boric acid, boric oxide, hydrogen fluoride, aluminum fluoride, ammonium fluoride, calcium fluoride, magnesium fluoride and cryolite.

[0031] According to the present invention, preferably, in step (2), the calcination temperature is 800-1800°C, preferably 1100-1500°C.

[0032] In the present invention, the alumina is substantially completely converted into α-A12O3 by calcination, for example, more than 90% is converted into α-A12O3, to obtain an α-A12O3 carrier.

[0033] The third aspect of the present invention provides an α-alumina carrier prepared by the preparation method of the α-alumina carrier.

[0034] The fourth aspect of the present invention provides a silver catalyst for producing ethylene oxide by ethylene oxidation, wherein the silver catalyst is prepared by impregnating the α-alumina carrier in a solution containing a silver compound.

[0035] In the present invention, the solution containing the silver compound may further contain other additives, such as alkali metal additives and rhenium additives. The silver catalyst may be prepared in a conventional manner.

[0036] A fifth aspect of the present invention provides an application of the silver catalyst in the epoxidation of ethylene to prepare ethylene oxide.

[0037] The present invention will be further described below in conjunction with embodiments, but the scope of the present invention is not limited to these embodiments.

[0038] Determination of catalyst performance:

[0039] The various silver catalysts of the present invention were tested for activity and selectivity using a laboratory microreactor evaluation device. The reactor used in the microreactor evaluation device was a stainless steel reaction tube with an inner diameter of 4 mm, which was placed in a heating jacket. The catalyst was loaded in a volume of 1 ml, with an inert filler at the bottom so that the catalyst bed was located in the constant temperature zone of the heating jacket.

[0040] The selective determination conditions adopted by the present invention are shown in Table 1:

[0041] Table 1 Reaction conditions of catalysts

[0042]

[0043] When the above reaction conditions are reached, the gas composition at the reactor inlet and outlet is continuously measured. The selectivity is calculated according to the following formula after the measurement results are corrected for volume shrinkage:

[0044]

[0045] Wherein, ΔEO is the difference in ethylene oxide concentration between the reactor outlet gas and the inlet gas, ΔCO2 is the difference in carbon dioxide concentration between the reactor outlet gas and the inlet gas, and the average of more than 10 groups of test data is taken as the test result of the day.

[0046] Comparative Example 1

[0047] 498g of trihydrate α-A12O3 (particle size of 50-150μm), 102g of pseudo monohydrate A12O3 and 2.5g of boric acid are placed in a mixer and mixed evenly, and then poured into a kneader. 120 ml of dilute nitric acid aqueous solution (nitric acid: water = 1:6, volume ratio) is poured into the kneader and kneaded into a paste that can be extruded. Finally, the paste is loaded into an extruder and extruded into a column with a diameter of 8.0mm and a length of 6.0mm. It is dried at 80-120℃ for more than 2 hours to reduce its free water content to less than 10% by weight. The dried column is placed in a high-temperature kiln, raised from room temperature to 1390℃ over 36 hours, and then kept at a constant temperature for 2 hours to obtain a white solid product. The XRD analysis of the solid shows that it is α-A12O3, and its relevant physical property data are shown in Table 2.

[0048] Example 1

[0049] 448g of α-alumina trihydrate (particle size of 50-150μm), 102g of pseudo-monohydrate A12O3, 2.5g of boric acid and 50g of single crystal alumina were put into a mixer and mixed evenly; 120ml of dilute nitric acid solution (nitric acid: water = 1:6, volume ratio) was poured into a kneader and kneaded into a paste that can be extruded. The paste was put into an extruder and extruded into a column with an outer diameter of 8.0mm and a length of 6.0mm. It was dried at 80-120℃ for more than 2 hours to reduce its free water content to less than 10wt%. The dried column was put into a high-temperature kiln, raised from room temperature to 1390℃ over 36 hours, and then kept at a constant temperature for 2 hours to obtain an α-A12O3 carrier. Its relevant physical properties data are shown in Table 2.

[0050] Example 2

[0051] 398g of α-alumina trihydrate (particle size of 50-150μm), 102g of pseudo-monohydrate A12O3, 2.5g of boric acid and 100g of single crystal alumina were put into a mixer and mixed evenly; 120 ml of dilute nitric acid solution (nitric acid: water = 1:6, volume ratio) was poured into a kneader and kneaded into a paste that can be extruded. The paste was put into an extruder and extruded into a column with an outer diameter of 8.0mm and a length of 6.0mm. It was dried at 80-120℃ for more than 2 hours to reduce its free water content to less than 10wt%. The dried column was put into a high-temperature kiln, raised from room temperature to 1390℃ over 36 hours, and then kept at a constant temperature for 2 hours to obtain an α-A12O3 carrier. Its relevant physical properties data are shown in Table 2.

[0052] Example 3

[0053] 298g of α-alumina trihydrate (particle size of 50-150μm), 102g of pseudo-monohydrate A12O3, 2.5g of boric acid and 200g of single crystal alumina were put into a mixer and mixed evenly; 120 ml of dilute nitric acid solution (nitric acid: water = 1:6, volume ratio) was poured into a kneader and kneaded into a paste that can be extruded. The paste was put into an extruder and extruded into a column with an outer diameter of 8.0mm and a length of 6.0mm. It was dried at 80-120℃ for more than 2 hours to reduce its free water content to less than 10wt%. The dried column was put into a high-temperature kiln, raised from room temperature to 1390℃ over 36 hours, and then kept at a constant temperature for 2 hours to obtain an α-A12O3 carrier. Its relevant physical properties data are shown in Table 2.

[0054] Example 4

[0055] 398g of β-alumina trihydrate (particle size of 50-150μm), 102g of pseudo-monohydrate A12O3, 2.5g of boric acid and 100g of single crystal alumina were put into a mixer and mixed evenly; 120 ml of dilute nitric acid solution (nitric acid: water = 1:6, volume ratio) was poured into a kneader and kneaded into a paste that can be extruded. The paste was put into an extruder and extruded into a column with an outer diameter of 8.0mm and a length of 6.0mm. It was dried at 80-120℃ for more than 2 hours to reduce its free water content to less than 10wt%. The dried column was put into a high-temperature kiln, raised from room temperature to 1390℃ over 36 hours, and then kept at a constant temperature for 2 hours to obtain an α-A12O3 carrier. Its relevant physical properties data are shown in Table 2.

[0056] Example 5

[0057] 398g of γ-alumina (particle size of 50-150μm), 102g of pseudo-monohydrate A12O3, 2.5g of boric acid and 100g of single crystal alumina were put into a mixer and mixed evenly; 120ml of dilute nitric acid solution (nitric acid: water = 1:6, volume ratio) was poured into a kneader and kneaded into a paste that can be extruded. The paste was put into an extruder and extruded into a column with an outer diameter of 8.0mm and a length of 6.0mm. It was dried at 80-120℃ for more than 2 hours to reduce its free water content to less than 10wt%. The dried column was put into a high-temperature kiln, raised from room temperature to 1390℃ over 36 hours, and then kept at a constant temperature for 2 hours to obtain an α-A12O3 carrier. Its relevant physical properties data are shown in Table 2.

[0058] Example 6

[0059] 398g of α-alumina trihydrate (particle size of 50-150μm), 102g of pseudo-monohydrate A12O3, 2.5g of calcium fluoride and 100g of single crystal alumina are placed in a mixer and mixed evenly; 120 ml of dilute nitric acid solution (nitric acid: water = 1:6, volume ratio) is poured into a kneader and kneaded into a paste that can be extruded. The paste is placed in an extruder and extruded into a column with an outer diameter of 8.0mm and a length of 6.0mm. It is dried at 80-120℃ for more than 2 hours to reduce its free water content to less than 10wt%. The dried column is placed in a high-temperature kiln, raised from room temperature to 1390℃ over 36 hours, and then kept at a constant temperature for 2 hours to obtain an α-A12O3 carrier. Its relevant physical properties data are shown in Table 2.

[0060] Example 7

[0061] 398g of α-alumina trihydrate (particle size of 50-150μm), 102g of pseudo-monohydrate A12O3, 2.5g of boron oxide and 100g of single-crystal alumina were put into a mixer and mixed evenly; 120 ml of dilute nitric acid solution (nitric acid: water = 1:6, volume ratio) was poured into a kneader and kneaded into a paste that can be extruded. The paste was put into an extruder and extruded into a column with an outer diameter of 8.0mm and a length of 6.0mm. It was dried at 80-120℃ for more than 2 hours to reduce its free water content to less than 10wt%. The dried column was put into a high-temperature kiln, raised from room temperature to 1390℃ over 36 hours, and then kept at a constant temperature for 2 hours to obtain an α-A12O3 carrier. Its relevant physical properties data are shown in Table 2.

[0062] Example 8

[0063] 398g of α-alumina trihydrate (particle size of 250-300μm), 102g of pseudo-monohydrate A12O3, 2.5g of boric acid and 100g of single crystal alumina were put into a mixer and mixed evenly; 120 ml of dilute nitric acid solution (nitric acid: water = 1:6, volume ratio) was poured into a kneader and kneaded into a paste that can be extruded. The paste was put into an extruder and extruded into a column with an outer diameter of 8.0mm and a length of 6.0mm. It was dried at 80-120℃ for more than 2 hours to reduce its free water content to less than 10wt%. The dried column was put into a high-temperature kiln, raised from room temperature to 1390℃ over 36 hours, and then kept at a constant temperature for 2 hours to obtain an α-A12O3 carrier. Its relevant physical properties data are shown in Table 2.

[0064] Example 9

[0065] 398g of α-alumina trihydrate (particle size of 5-10μm), 102g of pseudo-monohydrate A12O3, 2.5g of boric acid and 100g of single crystal alumina were put into a mixer and mixed evenly; 120 ml of dilute nitric acid solution (nitric acid: water = 1:6, volume ratio) was poured into a kneader and kneaded into a paste that can be extruded. The paste was put into an extruder and extruded into a column with an outer diameter of 8.0mm and a length of 6.0mm. It was dried at 80-120℃ for more than 2 hours to reduce its free water content to less than 10wt%. The dried column was put into a high-temperature kiln, raised from room temperature to 1390℃ over 36 hours, and then kept at a constant temperature for 2 hours to obtain an α-A12O3 carrier. Its relevant physical properties data are shown in Table 2.

[0066] Table 2 Physical properties of carrier

[0067] Carrier number Strength (N / grain) Water absorption (%) <![CDATA[Specific surface area (m 2 / g)]]> Comparative Example 1 57 42.8 0.91 Example 1 68 41.7 1.05 Example 2 64 40.2 1.12 Example 3 72 38.5 1.13 Example 4 77 40.1 1.21 Example 5 66 38.2 1.09 Example 6 81 41.0 1.01 Example 7 61 40.4 1.14 Example 8 59 40.6 1.07 Example 9 67 40.0 1.15

[0068] Catalyst preparation

[0069] Add 32.1g of ethylenediamine, 10.8g of ethanolamine and 179.8g of deionized water to a stirred glass beaker to obtain a mixed solution; slowly add 72.2g of silver oxalate to the mixed solution, keep the temperature below 40°C and continue stirring to completely dissolve the silver oxalate; then add 2.25mL of cesium nitrate aqueous solution (concentration of 0.03995g / mL, based on cesium atomic weight) and 2.78mL of ammonium perrhenate aqueous solution (concentration of 0.0162g / mL, based on rhenium atomic weight) in sequence, mix well to prepare 300g of impregnation solution for standby use.

[0070] Take 15g of the carriers prepared from the above Examples 1 to 9 and Comparative Example 1, respectively, put them into a vacuum glass container, and add the above silver amine impregnation solution to completely immerse the carrier. Evacuate to above 10mmHg, keep for about 15 minutes, and then remove the excess solution by leaching. Finally, place the impregnated carrier sample in an air flow at 350℃ and heat for about 2 minutes to prepare silver catalyst Examples 1 to 9 and Comparative Example 1.

[0071] The performance of the catalyst samples was measured using a microreactor evaluation device under the aforementioned process conditions for the corresponding silver catalysts obtained from the carriers in Examples 1 to 9 and Comparative Example 1. The data results on the 20th day after the start of the reaction are shown in Table 3.

[0072] Table 3 Catalyst performance test results

[0073] Catalyst No. Reaction temperature℃ Selectivity% Comparative Example 1 237.8 86.69 Example 1 232.1 88.11 Example 2 230.6 88.34 Example 3 230.4 88.23 Example 4 228.5 87.52 Example 5 229.8 88.01 Example 6 231.7 88.45 Example 7 229.2 88.07 Example 8 230.9 88.56 Example 9 230.0 88.13

[0074] As can be seen from Table 3, compared with Comparative Example 1 in which the silver catalyst was prepared using a carrier without adding single crystal alumina, according to the present invention, the silver catalyst prepared using an alumina carrier with single crystal alumina added under the same conditions has higher selectivity and stability.

[0075] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

[0076] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. An α-alumina carrier, characterized in that The α-alumina carrier comprises single-crystal alumina. Based on the total weight of the α-alumina carrier, the content of the single-crystal alumina is 0.1 to 50 wt %, preferably 1 to 40 wt %, and more preferably 5 to 35 wt %.

2. The α-alumina carrier according to claim 1, wherein The α-alumina carrier has the following characteristics: a specific surface area of ​​0.3 to 3.0 m 2 / g, water absorption not less than 25%, mechanical strength not less than 30N.

3. A method for preparing an α-alumina carrier, characterized in that: The steps include: (1) preparing a mixture comprising micron-sized alumina, pseudo-monohydrate alumina, a mineralizer and single-crystal alumina, and mixing the mixture with an acid solution; based on the total weight of the mixture, the content of the micron-sized alumina is 4.5-90wt%, the content of the pseudo-monohydrate alumina is 5-95wt%, the content of the mineralizer is 0.01-3wt%, and the content of the single-crystal alumina is 0.1-50wt%; (2) The material obtained in step (1) is kneaded, extruded, dried and calcined to obtain the α-alumina carrier.

4. The method for preparing an α-alumina carrier according to claim 3, wherein: In step (1), the particle size of the micron-sized aluminum oxide is 1 to 500 μm.

5. The method for preparing an α-alumina carrier according to claim 3, wherein: In step (1), based on the total weight of the mixture, the amount of micron-sized alumina added is 23-80wt%, the amount of pseudo-monohydrate alumina added is 18-75wt%, the amount of mineralizer added is 0.1-2.5wt%, and the amount of single-crystal crystalline alumina added is 1-40wt%, preferably 5-35wt%.

6. The method for preparing an α-alumina carrier according to claim 3, wherein: In step (1), the acid solution is a nitric acid aqueous solution, the volume ratio of nitric acid to water in the nitric acid aqueous solution is 1:1.25-10, preferably 1:2-8; the amount of the acid solution added is 5-50wt% based on the total weight of the mixture.

7. The method for preparing an α-alumina carrier according to claim 6, wherein: The pseudo alumina monohydrate and the acid solution are completely or partially replaced by aluminum sol.

8. The method for preparing an α-alumina carrier according to claim 3, wherein: In step (1), the micron-sized alumina is selected from at least one of α-alumina trihydrate, β-alumina trihydrate and γ-alumina; the mineralizer is selected from at least one of boric acid, boric oxide, hydrogen fluoride, aluminum fluoride, ammonium fluoride, calcium fluoride, magnesium fluoride and cryolite.

9. The method for preparing an α-alumina carrier according to claim 3, wherein: In step (2), the calcination temperature is 800-1800°C, preferably 1100-1500°C.

10. An α-alumina carrier obtained by the method for preparing an α-alumina carrier according to any one of claims 3 to 9.

11. A silver catalyst for producing ethylene oxide by ethylene oxidation, characterized in that: The silver catalyst is prepared by impregnating the α-alumina carrier according to any one of claims 1, 2 and 10 in a solution containing a silver compound.

12. Use of the silver catalyst according to claim 11 in preparing ethylene oxide by epoxidation of ethylene.

Citation Information

Patent Citations

  • Carrier of ethylene oxide silver catalyst, and its preparation method and application

    CN101007287A

  • High-efficiency silver catalyst for oxidizing ethylene into epoxy ethane

    CN1034678A

  • Silver catalyst carrier for epoxyethane production, preparation method and application thereof

    CN1634652A

  • Alumina catalyst supports containing barium salts

    EP0150238A1

  • Alumina compositions of improved strength useful as catalyst supports.

    US4428863A